2010
DOI: 10.1038/npp.2010.83
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Modafinil on Neural Circuits Regulating Emotion and Cognition

Abstract: Modafinil differs from other arousal-enhancing agents in chemical structure, neurochemical profile, and behavioral effects. Most functional neuroimaging studies to date examined the effect of modafinil only on information processing underlying executive cognition, but cognitive enhancers in general have been shown to have pronounced effects on emotional behavior, too. We examined the effect of modafinil on neural circuits underlying affective processing and cognitive functions. Healthy volunteers were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 47 publications
1
45
3
1
Order By: Relevance
“…Modafinil, which inhibits dopamine and norepinephrine transporters and decreases ϒ-aminobutyric acid also shows promise as a treatment for ADHD (131). In healthy adults, modafinil decreases amygdala activation during the viewing of fearful stimuli and boosts prefrontal cortical activation during executive functions (132). Again, this profile points to a drug with possible benefit for ADHD and associated emotion dysregulation.…”
Section: Treatmentmentioning
confidence: 95%
“…Modafinil, which inhibits dopamine and norepinephrine transporters and decreases ϒ-aminobutyric acid also shows promise as a treatment for ADHD (131). In healthy adults, modafinil decreases amygdala activation during the viewing of fearful stimuli and boosts prefrontal cortical activation during executive functions (132). Again, this profile points to a drug with possible benefit for ADHD and associated emotion dysregulation.…”
Section: Treatmentmentioning
confidence: 95%
“…However, discrepancies between behavioral performance and brain activation when examining modafinil are not unique to this study. A prior fMRI study in which modafinil (100 mg) was given daily for 7 days showed no effect of the medication on performance in a test of attentional control, but reduced ACC activation during task performance (Rasetti et al, 2010), also showing a mismatch between behavioral and fMRI effects of modafinil. Moreover, it is important to note that the mixed results found for the cognition-enhancing effects of modafinil on behavior in healthy participants often depend on the particular behavioral task, measures employed, and dosing regimens (Repantis et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There were 178 DRD2 GG/ HTR2A CC subjects, 33 DRD2 GG/HTR2A T carriers, 43 DRD2 T carriers/HTR2A CC, and 11 DRD2 T carriers/ HTR2A T carriers in this sample. The VAC is an eventrelated design task that has been used in several previous investigations (Blasi et al, , 2013aRasetti et al, 2010) to elicit brain activity during three levels of attentional control (low, intermediate, high) (see Supplementary Materials and Methods).…”
Section: Fmrimentioning
confidence: 99%